Cabozantinib Reverses Topotecan Resistance in Human Non-Small Cell Lung Cancer NCI-H460/TPT10 Cell Line and Tumor Xenograft Model - Lei, Zi-Ning; Teng, Qiu-Xu; Gupta, Pranav; Zhang, Wei; Narayanan, Silpa; Yang, Dong-Hua; Wurpel, John N. D.; Fan, Ying-Fang; Chen, Zhe-Sheng (Frontiers in Cell and Developmental Biology, 2021)
Cabozantinib is a small molecule tyrosine kinase receptor inhibitor, which could also inhibit the ABCG2 transporter function. Therefore, cabozantinib could re-sensitize cancer cells that are resistant to ABCG2 substrate drugs including topotecan. However, its reversal effect against topotecan resistance has not been tested in a topotecan-induced resistant cancer model. In this study, a new topotecan selected human non-small cell lung cancer (NSCLC) resistant cell model NCI-H460/TPT10 with ABCG2 overexpression and its parental NCI-H460 cells were utilized to investigate the role of cabozantinib in drug resistance. The in vitro study showed that cabozantinib, at a non-toxic concentration, could re-sensitized NCI-H460/TPT10 cells to topotecan by restoring intracellular topotecan accumulation via inhibiting ABCG2 function. In addition, the increased cytotoxicity by co-administration of cabozantinib and topotecan may be contributed by the synergistic effect on downregulating ABCG2 expression in NCI-H460/TPT10 cells. To further verify the applicability of the NCI-H460/TPT10 cell line to test multidrug resistance (MDR) reversal agents in vivo, and to evaluate the in vivo efficacy of cabozantinib on reversing topotecan resistance, a tumor xenograft mouse model was established by implanting NCI-H460 and NCI-H460/TPT10 into nude mice. The NCI-H460/TPT10 xenograft tumors treated with the combination of topotecan and cabozantinib dramatically reduced in size compared to tumors treated with topotecan or cabozantinib alone. The topotecan resistant phenotype of NCI-H460/TPT10 cell line and the reversal capability of cabozantinib in NCI-H460/TPT10 cells could be extended from in vitro cell model to in vivo xenograft model. Collectively, cabozantinib is considerably to be a potential approach in overcoming ABCG2-mediated MDR in NSCLC. The established NCI-H460/TPT10 xenograft model could be a sound clinical-relevant resource for future drug screening to eradicate ABCG2-mediated MDR in NSCLC.